Styrene Copolymerization Using a Metallocene-Mao Initiator System. Homo- and Copolymerization of Styrene with Some Cycloalkenes - Rabagliati-Canessa, F; Zapata-Ramirez, P; Canales-Arévalo, D (2013)
The copolymerization of styrene with cyclohexene, 1-methyl-1-cyclohexene, and norbornene using ethenylbisindenylzirconium dichloride and methylaluminoxane, Et(Ind)2ZrCl2-MAO, initiating systems has been tested. The results obtained with each styrene-cycloalkene couple, except styrene/norbornene, indicate a less effective polymerization process compared to styrene homopolymerization, in agreement with the electronic and steric effects present in each comonomer. The electronic I+ effects of substituent groups, depending on their placement, largely improve the polymerization process, while bulky groups on or near the vinyl carbon double bond of styrene decrease its effectiveness. The present study shows that the copolymers obtained are amorphous and their composition showed a lower abundance of comonomer units with respect to the initial feed. For comparison, the results of the copolymerization of styrene/(1-octadecene) using the same initiator system and polymerization process are included, a polymerization that indicates a more reactive process, and as the proportion of octadecene in the initial feed increases, it showed a crystalline fusion temperature as well as a Tg in the styrene region which can be attributed to the formation of block styrene/octadecene copolymers. © 2013 Springer-Verlag Berlin Heidelberg.